Exposing primary rat retina cell cultures to γ-rays: An in vitro model for evaluating radiation responses. (January 2018) - Gaddini, Lucia; Balduzzi, Maria; Campa, Alessandro; Esposito, Giuseppe; Malchiodi-Albedi, Fiorella; Patrono, Clarice; Matteucci, Andrea
Abstract: Retinal tissue can receive incidental γ-rays exposure during radiotherapy either of tumors of the eye and optic nerve or of head-and-neck tumors, and during medical diagnostic procedures. Healthy retina is therefore at risk of suffering radiation-related side effects and the knowledge of pathophysiological response of retinal cells to ionizing radiations could be useful to design possible strategies of prevention and management of radiotoxicity. In this study, we have exploited an in vitro model (primary rat retinal cell culture) to study an array of biological effects induced on retinal neurons by γ-rays. Most of the different cell types present in retinal tissue - either of the neuronal or glial lineages - are preserved in primary rat retinal cultures. Similar to the retina in situ, neuronal cells undergo in vitro a maturational development shown by the formation of polarized neuritic trees and operating synapses. Since 2 Gy is the incidental dose received by the healthy retina per fraction when the standard treatment is delivered to the brain, retina cell cultures have been exposed to 1 or 2 Gy of γ-rays at different level of neuronal differentiation in vitro : days in vitro (DIV)2 or DIV8. At DIV9, retinal cultures were analyzed in terms of viability, apoptosis and characterized by immunocytochemistry to identify alterations in neuronal differentiation. After irradiation at DIV2, MTT assay revealed an evident loss of cell viability and βIII-tubulin immunostaining highlighted a marked neuritic damage, indicating that survived neurons showed an impaired differentiation. Differentiated cultures (DIV8) appeared to be more resistant with respect to undifferentiated, DIV2 cultures, both in terms of cell viability and differentiation. Apoptosis evaluated with TUNEL assay showed that irradiation at both DIV2 and DIV8 induced a significant increase in the apoptotic rate. To further investigate the effects of γ-rays on retinal neurons, we evaluated the expression of synaptic proteins, such as SNAP25 and synaptophysin. WB and immunofluorescence analysis showed an altered expression of these proteins in particular when cultures were irradiated at DIV2. To evaluate the effect of γ-rays on photoreceptors, we studied the expression of rhodopsin in WB analysis and immunofluorescence. Our results confirm data from the literature that differentiated photoreceptors appear to be more resistant to irradiation respect to other retinal cell types present in cultures. The results obtained suggest that γ-rays exposure of primary retinal cultures may contribute to shed further light on the mechanisms involved in γ-radiation-induced neurodegeneration. Highlights: We suggest primary retinal cultures as a model to study the effects of γ-rays. Differentiated retinal neurons appear to be more resistant to γ-radiation. Photoreceptors appear to be more radioresistant than other retinal neurons.